Isolés et connectés.L’énergie dans les espaces protégés des Alpes françaises au défi de la transition environnementale - Marie Forget; Lionel Laslaz (Bulletin de l’Association de Géographes Français)
This article addresses, in different types of protected areas in the French Alps, the environmental transition through the production, consumption and potential impacts of various renewable energies. It also questions energy sobriety through “starry sky” initiatives and the night-time extinction of public lighting. Some protected mountain areas are poorly connected to the national electricity grid, which encourages the search for autonomous energy solutions leading to technical, social and legislative innovations. In this condition, actors have invented devices such as individual or collective self-consumption projects in isolated sites or Village Photovoltaic Plants born in the natural regional parks of the former Rhône-Alpes region. As such, protected spaces appear as uneven places for energy experimentation towards models of environmental transition.